Pengaruh Diet Beras Hitam, Kacang Merah dan Daun Kelor (Betamelor) Terhadap Perubahan Berat Badan Tikus Sprague-Dawley - Lina Yunita; Herianus Lalel; Stefanus Manongga (Poltekkes Kemenkes Kupang, 2020)
This study aims to analyze the effect of black rice, red beans and Moringa (betamelor) leaves on the body weight of Sprague-Dawley rats. This study is an experimental study in experimental animals, using factorial group design with a post test only control group. The research sample was 25 female Sprague-Dawley mice aged six months, grouped into one control group (K) and three treatment groups (P) with 80% (P1), 50% (P2) and 20% (P3) in the diet given. The intervention was carried out for 28 days. Weight was weighed every week while consumption measurements were taken every day. Standard feeding of BR II 5% of body weight per day made the weight of the control group rats (without betamelor) increase 21.7% after 28 days of intervention, higher than the P1, P2, and P3 groups, each of which gained weight 14.9%, 17.6% and 20.3%. After 28 days of intervention, there is significant differences between groups (p> 0.05).